Low Arousal Threshold: A Potential Bridge Between OSA and Periodic Limb Movements of Sleep - Wang Q (Dove Medical Press, 2021)
Qiaojun Wang,1,2,* Yezhou Li,3,* Jie Li,2 Jing Wang,1 Jiucheng Shen,1 Huaman Wu,1 Kaida Guo,1 Rui Chen1,2 1Sleep Center, Respiratory Department, The Second Affiliated Hospital of the Soochow University, Suzhou, People’s Republic of China; 2Sleep Center, Neurology Department, The Second Affiliated Hospital of the Soochow University, Suzhou, People’s Republic of China; 3School of Medicine, The University of Manchester, Manchester, UK*These authors contributed equally to this workCorrespondence: Rui ChenSleep Center, Respiratory Department, The Second Affiliated Hospital of the Soochow University, 1055 Sanxiang Road, Suzhou, 215004, People’s Republic of ChinaTel +86 512 67784176Email Chenruigood@126.comObjective: Periodic Limb Movements of Sleep (PLMS) is a poorly understood comorbidity with close association to Obstructive Sleep Apnea (OSA). The mechanistic link between the two is unclear. Recent studies on the latter have uncovered low respiratory arousal threshold as an important non-anatomical cause of the disorder. This study sought to investigate whether periodic limb movements are associated with the low respiratory arousal threshold (ArTH) in OSA.Methods: Retrospective data on 720 OSA patients (mean age = 47.0) who underwent Polysomnography (PSG) were collected. Using PLMS diagnostic criteria of PLMS index ≥ 15, patients were divided into the OSA-PLMS group (n=95) and the OSA-only group (n=625). Binary logistic regression analysis was used to examine the correlation between PLMS and the presence of low ArTH, classified using a predicted tool (developed by Edward et al) requiring meeting at least two of the three criteria: apnea-hypopnea index (AHI) < 30/h, nadir oxygen saturation (SaO2) > 82.5%, and fraction of hypopneas > 58.3%. The resulting model was validated in the external MrOS database.Results: The patients in the OSA-PLMS group tend to be older, with a higher prevalence of hypertension, diabetes, and stroke. PLMS was associated with age, diabetes, oxygen desaturation index, and low respiratory arousal threshold (OR=8.78 (4.73– 16.30), p< 0.001). When validated against the MrOS database, low ArTH remained a significant predictor of PLMS with an odds ratio of 1.33 (1.08– 1.64, p = 0.009).Conclusion: This is the first study that demonstrated a strong correlation between PLMS and low respiratory arousal threshold. This suggests a possible mechanistic link between the physical manifestation of PLMS and the non-anatomical low arousal threshold phenotype in OSA.Keywords: obstructive sleep apnea, periodic limb movements, low respiratory arousal threshold